Breastfeeding in China: a review - Xu, F.; Qiu, Liqian; Binns, Colin; Liu, X. (BioMed Central, 2009)
This review aims to describe changes in breastfeeding and summarise the breastfeeding rates, duration and reasons of discontinuing 'any breastfeeding' or 'exclusive breastfeeding' in P.R. China. Breastfeeding rates in China fell during the 1970s when the use of breast milk substitutes became widespread, and reached the lowest point in the 1980s. As a result many efforts were introduced to promote breastfeeding. The breastfeeding rate in China started to increase in the 1990s, and since the mid-1990s 'any breastfeeding' rates in the majority of cities and provinces, including minority areas, have been above 80% at four months. But most cities and provinces did not reach the national target of 'exclusive breastfeeding' of 80%. The 'exclusive breastfeeding' rates in minority areas were relatively lower than comparable inland provinces. The mean duration of 'any breastfeeding' in the majority of cities or provinces was between seven and nine months. The common reasons for ceasing breastfeeding, or introducing water or other infant food before four months, were perceived breast milk insufficiency, mother going to work, maternal and child illness and breast problems. Incorrect traditional perceptions have a strong adverse influence on 'exclusive breastfeeding' in less developed areas or rural areas. China is a huge country, geographically and in population size, and there is considerable ethnic diversity. Therefore breastfeeding rates in different parts of China can vary considerably.